EMPIRICAL EXPLICATION OF PSYCHOLOGICAL SIGNS OF NEUROTISATION AT JUNIOR VOLLEYBALL PLAYERS - Lazorko, Olha; Virna, Zhanna; Goshovskyi, Yaroslav; Melnychuk, Tetiana; Lunov, Vitalii (International Journal of Psychosocial Rehabilitation, 2020)
The problem of junior athletes’ neurotisation occupies one of the basic positions in the studies of their successful realization in sports. Explanations of the psychological characteristics influencing neurotisation can significantly deepen the understanding of neurotisation causes at junior athletes and complement the arsenal of early diagnosis and prevention of subclinical neurotic manifestations. Goal. The theoretical substantiation and an empirical explication of the psychological signs of junior volleyball players’ neurotisation. Materials and methods. The research was carried out on the basis of the children- youth sports school “Kolos”, Lutsk, namely, the junior volleyball players: 120 people aged of 16-17 years.